CASE 25th Anniversary Symposium on the Future of Europe. Issue 4 (December 2017) - Hartwell, Christopher
Abstract Over the past 25 years, the European project has seen many substantial changes and reforms: the transition process in Central and Eastern Europe (CEE) resulted in the accession to the EU of ten new Member States that were formerly communist, while the physical introduction of the Euro in 2002 presented the EU with a host of new macroeconomic challenges but provided hope for continuous and deeper integration processes. The 25th anniversary conference of the Center for Social and Economic Research (CASE) in Poland in November 2016 provided some concrete suggestions on how the future of Europe might play out.